2-Acetyl-3,5,5,9-tetramethyl-6,7,8,9-tetrahydro-5H-benzocyclohepten-7-one - Moha Berraho; Jean-Claude Daran; Essediya Lassaba; Noureddine Mazoir; Ahmed Benharref (Acta Crystallographica Section E, 2011)
The title compound, C17H22O2, was semi-synthesized from a mixture of α-atlantone (Z) and α-atlantone (E), which were isolated from the essential oil of the Atlas cedar (cedrus atlantica). The molecule consists of fused six- and seven-membered rings. The seven-membered ring is in a screw-boat conformation.